VD_FINDINFO Décision / 2012 / 234 vom 20. März 2012 - VD Tribunal cantonal (2012)
DISPOSITIONS PÉNALES DE LA LPP, ENQUÊTEEN GÉNÉRAL | 76 al. 2 LPP, 76 al. 3 LPP, 319 CPP (CH), 393 al. 1 let. a CPP (CH)